If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = 5x + 11 Reorder the terms: 3x = 11 + 5x Solving 3x = 11 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 3x + -5x = 11 + 5x + -5x Combine like terms: 3x + -5x = -2x -2x = 11 + 5x + -5x Combine like terms: 5x + -5x = 0 -2x = 11 + 0 -2x = 11 Divide each side by '-2'. x = -5.5 Simplifying x = -5.5
| 12x-3-7x+8=11(-1-5x)-4(-4+6x) | | 1=5(t-6) | | -x-54=-7x+54 | | X+2+x+2+x+2+X+2=12 | | 1+x+4+x+7+x+10=0 | | 0.02(n-550)=105 | | 4p+3q=41 | | 12.6x=56.7 | | 6n=3n-2+2(2n+1) | | -6s-11=-2s+5 | | 9k-26=6k | | 2x+7-26=17-4x+5 | | 2xy+60-5xy=x+10+y | | -2p-6=10-10p | | 26+2x=263 | | x-32=63-4x | | 0=-X^2-6X | | 6x+8=46 | | 12x^2y+8xy+4xy^2= | | 5x+16=8x-8 | | 5x-306=20 | | 18+x=x+11+12 | | 2xy-x+40-y=5y-20+xy | | T=141.68+.75M | | -7+4m=6n-5 | | 37xsquared+35x-14= | | .2x-25=18 | | -38+3x=38-x | | 4x^2+15x-4=f(x) | | ryan=rike | | 38+(7x+1)+(10x+22)=180 | | 10b^2+7=397 |